Intervention and research progress of gut microbiota-immune-nervous system in autism spectrum disorders among students - Zhou, Min; Niu, Baoming; Ma, Jiarui; Ge, Yukang; Han, Yanxin; Wu, Wenrui; Yue, Changwu (Frontiers in Microbiology, 2025)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by difficulties in social interaction and communication, repetitive and stereotyped behaviors, restricted interests, and sensory abnormalities. Its etiology is influenced by both genetic and environmental factors, with no definitive cause identified and no specific pharmacological treatments available, posing a significant burden on patients’ families and society. In recent years, research has discovered that gut microbiota dysbiosis plays a crucial role in the pathogenesis of ASD. The gut microbiota can influence brain function and behavior through the gut-brain axis via the nervous system, immune system, and metabolic pathways. On the one hand, specific gut microbes such as Clostridium and Prevotella species are found to be abnormal in ASD patients, and their metabolic products, like short-chain fatty acids, serotonin, and GABA, are also involved in the pathological process of ASD. On the other hand, ASD patients exhibit immune system dysfunction, with gut immune cells and related cytokines affecting neural activities in the brain. Currently, intervention methods targeting the gut microbiota, such as probiotics, prebiotics, and fecal microbiota transplantation, have shown some potential in improving ASD symptoms. However, more studies are needed to explore their long-term effects and optimal treatment protocols. This paper reviews the mechanisms and interrelationships among gut microbiota, immune system, and nervous system in ASD and discusses the challenges and future directions of existing research, aiming to provide new insights for the prevention and treatment of ASD.